FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PERBANKAN PADA MASA PANDEMI - Aslah, Titi; Tandean, Vivi Adeyani (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2022)
This research is very important to do because it wants to see the financial condition of our banks on the Indonesia Stock Exchange, and the impact that occurs when the crisis and pandemic phenomena occur. The purpose of this research is to find out the impact and financial conditions that are happening when the pandemic and crisis occur, as well as to find out what methods and policies are appropriate to save banking from crises and pandemics. This research uses descriptive analysis method. From the results of the study, it can be concluded that the financial ratio that has the most influence on the financial performance of IDX banks is the Capital Adequacy Ratio (CAR), which is a capital ratio that shows the bank's ability to provide funds for business development purposes and accommodate the risk of loss of funds caused by tire operations. The Ner Interest Margin (NIM) ratio shows the ratio of bank interest income (loan interest income minus deposit interest costs) to outstanding loans, this ratio shows the bank's ability to obtain operating income, and Third Party Funds Ratio (TPF) If the amount of TPF increases, the funds There will be more and more that can be processed by the Bank so that it can get a lot of profit, high interest income is used by the Bank to increase lending so that the profits obtained are high.